2014
DOI: 10.1186/1471-2334-14-173
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of renal impairment associated with tenofovir use amongst people living with HIV in India: A comparative cohort analysis between Western India and United Kingdom

Abstract: BackgroundData on the renal safety of Tenofovir (TDF) in Low and Middle Income Countries (LMICs) is scarce. We compared development of various forms of renal impairment with use of TDF-containing antiretroviral therapy (ART) between a cohort from the Institute of Infectious Diseases (IID) Pune, Western India and the Royal Free Hospital (RFH) London, UK.MethodsThis is a retrospective analysis of change in estimated glomerular filtration rates (eGFRs) at 6, 12 and 24 months post TDF initiation using the Modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
2
15
1
Order By: Relevance
“…The majority of patients had normal renal function at baseline. Just over six percent of these patients developed renal dysfunction during follow up, which is similar to recent studies done in Asia [ 12 , 13 ], but in the majority of these patients this was not severe enough to warrant a change in therapy. Only four patients (0.3%) progressed to severe renal dysfunction needing a change to an alternative ART regimen, with these findings mirroring those from elsewhere[ 14 ].These overall results are in line with previous studies which concluded that the clinical magnitude of renal toxicity during TDF-based ART is modest[ 6 ].This low incidence of renal toxicity is further confirmed by more recent publications from Africa and Asia [ 15 , 16 ]although differences in definitions of renal dysfunction and duration on TDF-based ART make it difficult to compare findings from one study to another.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of patients had normal renal function at baseline. Just over six percent of these patients developed renal dysfunction during follow up, which is similar to recent studies done in Asia [ 12 , 13 ], but in the majority of these patients this was not severe enough to warrant a change in therapy. Only four patients (0.3%) progressed to severe renal dysfunction needing a change to an alternative ART regimen, with these findings mirroring those from elsewhere[ 14 ].These overall results are in line with previous studies which concluded that the clinical magnitude of renal toxicity during TDF-based ART is modest[ 6 ].This low incidence of renal toxicity is further confirmed by more recent publications from Africa and Asia [ 15 , 16 ]although differences in definitions of renal dysfunction and duration on TDF-based ART make it difficult to compare findings from one study to another.…”
Section: Discussionsupporting
confidence: 85%
“…A considerable number of patients had clinically meaningful, mild CKD, with no patients with moderate or severe CKD or kidney failure (≥stage 3) CKD in this 3-year follow-up study. Our CKD incidence of 2.2–12.4% was not low, compared with previous studies in Asian countries, despite a lack of consistency in definition and inclusion population 1331323334…”
Section: Discussioncontrasting
confidence: 84%
“…Numerous reports have documented higher incidence of CKD in Asian PLHIV compared with European and US cohorts. In a study from India, PLHIV on a TDF‐based regimen had higher and faster decline in the eGFR compared with PLHIV in the United Kingdom . In a 12‐year observational cohort in Tokyo, incidence of CKD was 20.6 per 1000 years of follow‐up and was strongly associated with use of TDF .…”
Section: Discussionmentioning
confidence: 99%
“…In a study from India, PLHIV on a TDF-based regimen had higher and faster decline in the eGFR compared with PLHIV in the United Kingdom. 16 In a 12-year observational cohort in Tokyo, incidence of CKD was 20.6 per 1000 years of follow-up and was strongly associated with use of TDF. 4 Chronic kidney disease has been reported among 7.3% of Vietnamese PLHIV on ART.…”
Section: Numerous Reports Have Documented Higher Incidence Of Ckd Inmentioning
confidence: 99%